Penguatan Literasi Hukum Hak-hak Anak Korban Kekerasan Seksual Berdasarkan Undang-undang Tindak Pidana Kekerasan Seksual - Dudy, Aryadi Almau; Ashady, Suheflihusnaini; Ahwan, Ahwan; Nirmala, Atika Zahra; Taufik, Zahratul’ain; Rahmania, Nunung (Universitas Pahlawan Tuanku Tambusai, 2026)
Sexual violence is a serious violation of human dignity and the fundamental rights of every individual. This act not only causes physical injury but also leads to psychological trauma and long-term social consequences for victims. In the perspective of legal philosophy, sexual violence against children constitutes a form of dehumanization that disregards human worth and substantive justice, aligning with the view of natural law theory that every person is entitled to protection and respect. Therefore, legal protection for child victims of sexual violence represents the State’s responsibility as mandated by the Constitution. The urgency of this community service initiative is grounded in the idea that law is not merely a set of written rules, but also a means of empowering society, as emphasized in Satjipto Rahardjo’s theory of progressive law. By strengthening legal literacy, communities can function as legally aware subjects. Collaboration between society, law-enforcement authorities, and social institutions is essential to building a responsive and humanistic child-protection system in accordance with Lawrence Friedman’s legal system theory.